Comparison between microscopically and macroscopically hippocampal activity in epilepsy patients - Sillekens, Lonieke; van Straaten, Ilse (Student Undergraduate Research E-journal!, 2015)
Thirty percent of epilepsy patients do not respond to adequate antiepileptic drugs and for those patients, epilepsy surgery is an option. The invasive measurements of depth electroencephalography are used to localize the seizure onset zone, which is later resected to achieve seizure freedom, but are complicated because of their invasive nature. In this study, dEEG measurements of the hippocampus were compared to anatomically-matched virtual electrodes reconstructed out of MEG signals, to investigate whether restating-state non-invasive measurements reflect resting-state activity that is measured invasively with dEEG Our findings indicate MEG being a possible clinical replacement for depth EEG in the future.